509 Sick leave by occupational accident: a retrospective epidemiological study. (24th April 2018) - Brito, RV; Batalini, VR; Lemos, AFA; Zafalon, AES; Galhardi, CM; Ferreira, LR
Abstract : Introduction: Wounds, illness and deaths caused in the work environment cost $21, 46 billion (2015) in Brazil, according to the Secretariat of Labour Inspection of Ministry of Labour. Contributing to this overview, the Sick Leave is a benefit granted by Brazilian National Social Security Institute (INSS), to workers who are victims of occupational accidents and become temporarily unable for work. In this context, the present study aims to evaluate the epidemiological profile of workers receiving sick leave by occupational accident, correlating data about illnesses, gender, occupational location and age group. Methods: A retrospective study based on analyses of 4.035 patients who requested sick leave by occupational accident from the Brazilian National Social Security Institute (INSS), characterising the age, gender, prevalence of urban and rural workers, more prevalent diseases associated with the occupational accidents through the ICD-10, from January 2014 to March 2017. Results: The study showed that the majority of 4.035 victims of the accidents with the benefit were male (73, 08%), associated with urban jobs (91, 82%) ranging from 30–39 years-old (28, 52%); rural jobs represented 8, 17% ranging from 45–54 years-old. The fractures of upper limb represented 25, 41% of all benefits, followed by fractures of lower limb (18, 33%), diseases of upper limb not associated with fractures (12, 48%) and diseases of lower limb not associated with fractures (6, 16%). Discussion: The profile of workers who were victims of occupational accidents that received disability benefits from INSS revealed that the majority of beneficiaries were male adults, working in urban jobs ranging from 30–39 years-old, associated mainly with diseases of upper limbs. These data should help in the implementation of measures to prevent the loss of work capacity caused by occupational accidents involving Brazilian workers. It's expected this prevent measures decrease the costs related to work environment.